Confirming the contribution and genetic spectrum of de novo mutation in infantile spasms: Evidence from a Chinese cohort. Issue 6 (5th May 2021) - Liu, Liying; Liu, Fang; Wang, Qiuhong; Xie, Hua; Li, Zhengchang; Lu, Qian; Wang, Yangyang; Zhang, Mengna; Zhang, Yu; Picker, Jonathan; Cui, Xiaodai; Zou, Liping; et al.
Abstract: Objective: We determined the yield, genetic spectrum, and actual origin of de novo mutations (DNMs) for infantile spasms (ISs) in a Chinese cohort. The efficacy of levetiracetam (LEV) for STXBP1 ‐related ISs was explored also. Methods: Targeted sequencing of 153 epilepsy‐related candidate genes was applied to 289 Chinese patients with undiagnosed ISs. Trio‐based amplicon deep sequencing was used for all DNMs to distinguish somatic/mosaic mutations from germline ones. Results: Total of 26 DNMs were identified from 289 recruited Chinese patients with undiagnosed ISs. Among them, 24 DNMs were interpreted as pathogenic mutations based on American College of Medical Genetics and Genomics guidelines, contributing to 8.3% (24/289) of diagnosis yield in the Chinese IS cohort. CDKL5 and STXBP1 are the top genes with recurrent DNMs, accounting for 3.1% (9/289) of yield. Further deep resequencing for the trio members showed that 22.7% (5/22) of DNMs are actually somatic in the proband or a parent. These somatic carriers presented milder seizure attacks than those with true germline DNMs. After treatment with LEV for half a year, three patients with DNM in STXBP1 showed improved clinical symptoms, including seizure‐free and normal electroencephalogram, except for a patient with a second DNM in DIAPH3 . Significance: Our study confirmed the contribution and genetic spectrum of DNMs in Chinese IS patients. Somatic mutation account for a quarter of DNMs in IS cases. Treatment with LEV improved the prognosis of STXBP1 ‐related ISs. Abstract : The contribution and genetic spectrum of de novo mutations (DNMs) was confirmed in infantile spasms (ISs). Somatic mutation accounted for 22.7% of DNMs in IS patients. Treatment with levetiracetam improved the prognosis of STXBP1‐related ISs.